Hubungan Dukungan Keluarga dengan Kualitas Hidup Penderita Tuberkulosis: Relationship of Family Support with Quality of Life of Patients Tuberculosis - Saputra, Candra (Jurnal Surya Medika (JSM), 2022)
Tuberculosis (TBC) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. The phenomenon that is found in today’s society is that there are still family members who are afraid to be close to someone who has tuberculosis, so that excessive caution appears, for example, such as alienating the patient, reluctant to talk, and if close the patient will immediately cover his nose and so on. This study aims to determine "The Relationship between Family Support and Quality of Life of Tuberculosis Patients". This research method uses the method Literature Review. In this study, there are 6 journals that have been screened with criteria inclusion ranging from a sample of 41-96 respondents, with 1 study design, namely cross-sectional, published in a 2017-2020 journal and written in Indonesia. Based on the results of the study using a Literature Review of 6 journals analyzed, it was found that family support and quality of life of respondents were in the good dominant category and results statistically from 6 journals p-value 0.00 < 0.05 there was a relationship between family support and quality of life for tuberculosis patients. The results of the analysis of 6 research journals Literature Review that the higher the family support for TB patients, the better the level of quality of life and shows that there is a very significant relationship between family support and the quality of life of people with tuberculosis.